Incidence of Antibiotic Resistant Bacteria in Poultry and Livestock in Dhaka City - Rahman, MH; Rahman, MM; Sultana, R; Kabir, MS (Stamford Journal of Microbiology, 2022)
Antimicrobial resistance is a concern for humans and animals all over the world. Indiscriminate use of antibiotics in livestock and poultry has become one of the major causes of antimicrobial resistance development in microorganisms. The aim of the study was to determine the antimicrobial resistance patterns of bacteria isolated from raw meat, intestine, feces and feed of farm chicken, cow and local chicken. Samples were collected from different retail shops at Malibagh area in Dhaka City, Bangladesh. Bacterial load was enumerated, potentially pathogenic bacteria were identified and antibiogram was determined following standard methods. A total of 43 bacterial isolates were identified from different samples which were Escherichia coli, Enterobacter, Citrobacter, Klebsiella, Providencia and Acinetobacter spp. Eight types of antibiotics such as, Ampicillin-10μg, Gentamicin-10μg, Amikacin-10μg, Amoxicillin-10μg, Ceftriaxone-30μg, Imipenem-10μg, Chloramphenicol-30μg and Tetracycline-30μg were used to determine the antibiotic sensitivity pattern of isolated bacteria. The antibiotic resistance pattern of bacteria isolated from feed and feces samples of cow and chicken were found to be similar. Isolated bacteria from chicken meats showed higher antimicrobial resistance (80-100%) against Ampicillin-10μg, Imipenem-10μg and Amoxicillin-10μg compared to cow meat isolates. The incidence of antibiotic resistant bacteria is a threat to animals, food handlers and consumers if they are being infected by these antibiotic resistant pathogenic bacteria. Stamford Journal of Microbiology, Vol.12 (1) 2022: 37-42